Structural and biophysical investigations into ubiquitin binding proteins - Garner, Thomas Peter (2011)
The complicated task of interpreting the many ubiquitin signals is mediated by specific ubiquitin binding domains. The investigations discussed in this thesis focus on two very different ubiquitin binding domains.